Konvergensi Media dalam Model Produksi dan Distribusi Konten Indonesiana TV - Imansari, Nitra Galih; Al-Faizah, Nabila Muthmainnah; Adiba, Mirza Azkia Muhammad (PRoMEDIA, 2025)
This study aims to analyze the transformation of content production and distribution models at Indonesiana.TV, as a representation of media convergence practices within Indonesia’s public broadcasting institutions. Operated under the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), Indonesiana.TV demonstrates how public broadcasters adapt to the digital ecosystem through technological integration, cross-regional collaboration, and multiplatform content strategies. Using a qualitative single-case study approach, data were collected through in-depth interviews with production and editorial managers, participatory observation of newsroom and digital publication processes, and document analysis of video archives and social media uploads. The findings reveal three key dimensions of media convergence: (1) a transformation of the production model into a collaborative and curatorial system involving regionalunits, creative communities, and independent production houses; (2) a shift in distribution strategies toward multiplatform content repackaging that aligns with digital audience behavior; and (3) the evolution of editorial management into a participatory digital newsroom model. These findings indicate that media convergence in Indonesiana.TV extends beyond technological adaptation—it represents an epistemic and institutional shift toward collaboration, openness, and participatory values in digital broadcasting. The study confirms the applicability of Jenkins’ Convergence Culture (2006) and Helmond’s Platformization of Media (2015) within the Indonesian context and provides insights into developing a data-driven, collaborative, and culturally grounded public broadcasting management model in the era of convergence.